Coins Are Cold and Cards Are Caring: The Effect of Pregiving Incentives on Charity Perceptions, Relationship Norms, and Donation Behavior - Yin, Bingqing (Miranda); Li, Yexin Jessica; Singh, Surendra (Journal of Marketing, 2020)
Charities often include low-value monetary (e.g., coins) and nonmonetary (e.g., greeting cards) pregiving incentives (PGIs) in their donation request letters. Yet little is known about how donors respond to this marketing strategy. In seven studies, including two large-scale field experiments, the authors demonstrate that the effectiveness of PGIs depends on the organization’s goals. People are more likely to open and read a letter containing a monetary PGI (vs. a nonmonetary PGI or no PGI). In addition, monetary PGIs increase response rates in donor acquisition campaigns. However, the return on investment for direct mail campaigns drops significantly when PGIs are included. Furthermore, average donations for appeals with a nonmonetary PGI or no PGI are similar, while those with a monetary PGI are actually lower than when a nonmonetary PGI or no PGI is included. This is because monetary PGIs increase exchange norms while decreasing communal norms. This effect remains significant when accounting for alternative explanations such as manipulative intent and the anchoring and adjustment heuristic.